Pengembangan Buku Panduan Penulisan Artikel Publikasi Ilmiah bagi Mahasiswa Sarjana Terapan Jurusan Teknik Sipil Polines - Devilito, Rio (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The aims of this research are (1) to describe the need and urgency of a guide for writing scientific publication articles for students and (2) to develop a guide for writing scientific publication articles for students of the Civil Engineering Department. This study uses a research and development approach. The validation of this guide is carried out in terms of content/material feasibility, presentation, language, and graphics. The target user guide for writing articles for scientific publications is Bachelor of Applied Civil Engineering students. The results of this study are (1) guidelines for writing scientific publication articles are needed to support the skills of Civil Engineering students to be productive in writing scientific publication articles and (2) guidelines for writing scientific publication articles for students of the Civil Engineering Department are developed based on regulations, systematics, and based writing ethics so that the results can be accounted for and have a scientific contribution in vocational tertiary institutions.